2018
DOI: 10.1073/pnas.1719405115
|View full text |Cite
|
Sign up to set email alerts
|

WDR5 modulates cell motility and morphology and controls nuclear changes induced by a 3D environment

Abstract: Abstract:Cell migration through extracellular matrices requires nuclear deformation, which depends on nuclear stiffness. In turn, chromatin structure contributes to nuclear stiffness, but the mechanosensing pathways regulating chromatin during cell migration remain unclear. Here, we demonstrate that WD repeat domain 5 (WDR5), an essential component of H3K4 methyltransferase complexes, regulates cell polarity, nuclear deformability and migration of lymphocytes in vitro and in vivo, independent of transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 53 publications
11
61
0
Order By: Relevance
“…Aligning with these studies, we have previously described that epigenetic changes related with closed chromatin conformation alter the mechanical properties and shape of nuclei from lymphocytes and leukemia cells [21]. Now, we have extended these results and described how increased levels of a euchromatin marker (H3K4 methylation) are linked to the biomechanical properties of isolated nuclei from cells moving in 3D environments [22].…”
Section: Chromatin Contribution To Nuclear Stiffnessmentioning
confidence: 53%
See 2 more Smart Citations
“…Aligning with these studies, we have previously described that epigenetic changes related with closed chromatin conformation alter the mechanical properties and shape of nuclei from lymphocytes and leukemia cells [21]. Now, we have extended these results and described how increased levels of a euchromatin marker (H3K4 methylation) are linked to the biomechanical properties of isolated nuclei from cells moving in 3D environments [22].…”
Section: Chromatin Contribution To Nuclear Stiffnessmentioning
confidence: 53%
“…to demonstrate that chromatin structure contributes, independently of its transcriptional activity, to the shape, size and mechanical properties that govern nuclear deformability [13,23,24]. Through atomic force microscopy (AFM) and nuclear multiparticle tracking (NMPT) we have recently revealed that nuclei from cells in suspension or from cells in 2D culture present different stiffness and viscosity than nuclei from cells moving in 3D [22]. Our findings suggest that chromatin decompaction induced by confined conditions decreases nuclear stiffness.…”
Section: Chromatin Contribution To Nuclear Stiffnessmentioning
confidence: 72%
See 1 more Smart Citation
“…3D collagen matrices induced methylation of histone 3, lysine 4 residue (H3K4) by methyltransferases, and this methylation increased as a function of collagen density. H3K4 methylation in T cells in 3D environments was associated with less dense chromatin structure, deformable and less stiff nuclei, and lower nuclear viscosity . This mechanism operated through the WD repeat‐containing protein 5 (WDR5) subunit of methyltransferases.…”
Section: Mechanical Force In the Service Of Leukocyte Functionmentioning
confidence: 99%
“…H3K4 methylation in T cells in 3D environments was associated with less dense chromatin structure, deformable and less stiff nuclei, and lower nuclear viscosity. 66 This mechanism operated through the WD repeat-containing protein 5 (WDR5) subunit of methyltransferases. Importantly, the cytoskeleton was shown to couple the methylation of H3K4 through WDR5 in a 3D environment, shedding light on a novel mechanotransducing role for WDR5 in T cells.…”
Section: Force In the Regulation Of Leukocyte Rolling And Diapedesismentioning
confidence: 99%